Very Early Cytomegalovirus Infection After Renal Transplantation: A Single-Center 20-Year Perspective. Issue 1 (March 2019) - Jorgenson, MR; Descourouez, JL; Astor, BC; Smith, JA; Aziz, F; Redfield, RR; Mandelbrot, DA
Background: Cytomegalovirus (CMV) infection risk in the first month after transplantation is felt to be minimal; however, the epidemiology has not been specifically investigated, particularly in the modern era of potent immunosuppressive regimens and universal CMV prophylaxis. Objective: The aim of this study was to describe the incidence of and risk factors associated with CMV occurring less than 30 days after transplant and evaluate the effect of very early CMV on outcomes. Methods: Retrospective, single-center study of adult renal transplant (RTX) recipients between January 1, 1994 and December 31, 2014. Results: A total of 5225 patients who received a renal transplant in the study time period were reviewed for the presence of CMV infection occurring less than 30 days after transplant. Of these, only 14 patients demonstrated this finding for an overall incidence of 0.27%. Half of these patients were considered to be at heightened risk due to being a recipient of a non-primary transplant or on chronic immunosuppression. This left seven patients without known risk factors for very early CMV to evaluate. In this group, time from transplant to CMV infection was 13.5 ± 7 days. The majority (57.1%, n = 4) were high-risk serostatus (CMV D+/R−) and occurred in the valganciclovir era (71.4%, n = 5). Lymphocyte-depleting induction predominated (57.1%, n = 4). Average cold ischemic time (CIT) was 19.7 ± 7.7 hours. Three patients had post-operative complications, two required exploratory-laparotomy for hemorrhage. When evaluating outcomes, 43% (n = 3) had subsequent episodes of CMV infection, 28.6% (n = 2) developed rejection, and 28.6% (n = 2) died. Outcomes between patients with CMV infection less than 30 days and those with CMV infection more than 30 days after transplant were not significantly different. Conclusions: In our review of over 5000 kidney transplants, the incidence of CMV infection in the first 30 days after renal transplant is 0.2%. Notable common patient characteristics include hemorrhage requiring re-operation and prolonged CIT. Outcomes were similar to CMV occurring more than 30 days after transplant. This study should provide the clinician with some reassurance; despite potent immunosuppressive therapy, CMV infection in the first 30 days is unlikely.